2014
DOI: 10.1093/europace/euu281
|View full text |Cite
|
Sign up to set email alerts
|

Haemodynamic consequences of targeted single- and dual-site right ventricular pacing in adults with congenital heart disease undergoing surgical pulmonary valve replacement

Abstract: AimsThe purpose of this study was to create an epicardial electroanatomic map of the right ventricle (RV) and then apply post-operative-targeted single- and dual-site RV temporary pacing with measurement of haemodynamic parameters. Cardiac resynchronization therapy is an established treatment for symptomatic left ventricular (LV) dysfunction. In congenital heart disease, RV dysfunction is a common cause of morbidity—little is known regarding the potential benefits of CRT in this setting.Methods and resultsSixt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Temporary RV-CRT was applied by atrial-synchronized RV free wall pacing in bipolar configuration from 2 closely spaced electrodes placed at the border between the inflow and outflow parts in the proximity of the tricuspid annulus. This region has been reported as the site of latest activation in the postrepair tetralogy of Fallot patients with RBBB 12 (Figure 1). Sensed (echocardiographic evaluation) or paced (catheterization) AV delays were set to achieve maximum shortening of the QRS complex through fusion of the intrinsic and paced ventricular depolarization waves.…”
Section: Rv Resynchronizationmentioning
confidence: 81%
See 1 more Smart Citation
“…Temporary RV-CRT was applied by atrial-synchronized RV free wall pacing in bipolar configuration from 2 closely spaced electrodes placed at the border between the inflow and outflow parts in the proximity of the tricuspid annulus. This region has been reported as the site of latest activation in the postrepair tetralogy of Fallot patients with RBBB 12 (Figure 1). Sensed (echocardiographic evaluation) or paced (catheterization) AV delays were set to achieve maximum shortening of the QRS complex through fusion of the intrinsic and paced ventricular depolarization waves.…”
Section: Rv Resynchronizationmentioning
confidence: 81%
“…RV or biventricular pacing improves short-term hemodynamics in both children and adults with congenital heart disease and RBBB. [8][9][10][11][12][13] The impact of RV-CRT on RV mechanics and contraction efficiency has, however, never been studied despite the fact that pulmonary RV dysfunction and failure are common sources of morbidity and reason for reinterventions in both pediatric and adult congenital heart disease. The present report gives insights into the potential role of RV-CRT in this specific patient group.…”
mentioning
confidence: 99%
“…On the other hand, several studies showed the strength of relatively simple measures of dyssynchrony, such as apical rocking and septal flash do improve prediction of CRT response [48][49][50] . Further improvements were made by using the analysis of strain patterns 51 , resulting in parameters such as CURE 52 , septal systolic rebound stretch 37,53 , and systolic stretch index 47 .…”
Section: Assessment Of Mechanical Dyssynchronymentioning
confidence: 99%
“…LBBB was present 50 . A study in patients with congenital heart disease and RBBB found that pacing from a site of late activation in the RV yielded superior haemodynamic benefit over RV apical pacing, underlining the importance of exploring alternative lead locations 51 . Pacing the RV from a site of late activation was also found to be beneficial in other studies 52,53 .…”
mentioning
confidence: 99%
See 1 more Smart Citation